The Relationship Between Maternal Education Level and Stunting: Literature Review - Rusdi D Rusdi D; Nurhasan Syah; Elsa Yuniarti (Postgraduate, University of Mataram, 2024)
Children who are shorter than their peers due to malnutrition before and after birth are called stunting. Stunting occurs when a married adolescent woman has a low socioeconomic status and education level, thus increasing psychological stress caused by limited human resources and childcare so that child growth and development are not optimal. One important factor that influences the prevalence of stunting in early childhood and toddlers is maternal education. Increasing public awareness of the importance of maternal education in preventing stunting and improving the quality of child health. This review study aims to present evidence on the correlation between stunting and maternal education and to determine the extent to which maternal education affects the nutritional status and growth of children, especially stunting. With these objectives, this study is expected to make a significant contribution to understanding and addressing stunting problems in the community. The literature review method and the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) meta-analysis process were used throughout the investigation. There is a correlation between stunting and maternal education based on many research findings. In conclusion, education level, low maternal age, poor toddler care and nutritional intake during pregnancy are associated with stunting